2021
DOI: 10.1039/d1ra02746h
|View full text |Cite
|
Sign up to set email alerts
|

A photosensitive metal–organic framework having a flower-like structure for effective visible light-driven photodegradation of rhodamine B

Abstract: Using the method of adding morphological control agent-trifluoroacetic acid (TFA), a flower-like porphyrin-based metal organic framework can be prepared, which shows a good effect on the photocatalytic degradation of rhodamine B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
(56 reference statements)
1
24
0
Order By: Relevance
“…The photocatalyst sample (5 mg) and different types of dye molecules dissolved in DMA solution (10 mg L −1 or 20 mg L −1 , 100 mL) were mixed in a photoreactor. [23][24][25] The solution was stirred magnetically for 30 min in the dark to achieve the adsorption/desorption equilibrium. Then, the mixture was exposed to a 300 W Xe lamp placed at a distance of 12 cm under an O 2 atmosphere.…”
Section: Photocatalytic Degradation Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalyst sample (5 mg) and different types of dye molecules dissolved in DMA solution (10 mg L −1 or 20 mg L −1 , 100 mL) were mixed in a photoreactor. [23][24][25] The solution was stirred magnetically for 30 min in the dark to achieve the adsorption/desorption equilibrium. Then, the mixture was exposed to a 300 W Xe lamp placed at a distance of 12 cm under an O 2 atmosphere.…”
Section: Photocatalytic Degradation Measurementsmentioning
confidence: 99%
“…More importantly, some functional organic ligands or open metal sites can be introduced into MOF frameworks by direct synthetic or post-synthetic methods to provide active catalytic sites, 18–20 which are conducive to the degradation of organic dyes. 21,22 For example, [Cu 2 (TCPP)]·3H 2 O (H 4 TCPP = tetrakis(4-carboxyphenyl)porphyrin), 23,24 [ZnL(BPY)]·H 2 O (BPY = 2,2′-bipyridine, H 2 L = cis -1,3-dibenzyl-2-imidazolidone-4,5-dicarboxylic acid) and [ZnL(BPA)]·H 2 O (BPA = 1,2-bis(4-pyridyl)ethane) 25 have been reported to effectively degrade RhB + , MB + and MO − under visible light. 26 Although a lot of investigations have been conducted on the adsorption of organic dyes and remarkable performance has been achieved in the photocatalytic degradation of organic dyes with MOFs, 27 it is still a huge challenge to investigate more efficient catalysts to improve the adsorption and degradation performance of organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional microbial treatment for wastewater deters from low efficacies due to the increased salt content in dye-containing water and low biodegradability of these dyes. , Over time, various other methods including membrane separation, oxidation, physical adsorption, and biological treatment have been developed for countering this problem. , However, visible light-mediated dye degradation through the photocatalytic pathway seems to be the best fit in view of reduction in chemical usage, less energy consumption, and minimum waste generation. Since the discovery of photocatalytic performance of MOF-5, these organic–inorganic hybrids are employed as promising catalysts for the degradation of the organo-toxins under visible light and regarded as an eco-friendly route to environmental remediation with augmented efficiency over traditional metal sulfides/oxides. Particularly, the heterogeneous nature of MOFs promises highly efficient and multicyclic usage without much loss in catalytic activity, , in which mixed-ligand frameworks are extensively used for photodegradation of lethal organic dyes. For example, a Zn­(II)-based framework (BUT-206) is recently used for the photodegradation of cationic dyes within 120 min with 92.5% catalytic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of photocatalytic performance of MOF-5, these organic−inorganic hybrids are employed as promising catalysts for the degradation of the organo-toxins under visible light and regarded as an eco-friendly route to environmental remediation with augmented efficiency over traditional metal sulfides/ oxides. 28−30 Particularly, the heterogeneous nature of MOFs promises highly efficient and multicyclic usage without much loss in catalytic activity, 31,32 in which mixed-ligand frameworks are extensively used for photodegradation of lethal organic dyes. For example, a Zn(II)-based framework (BUT-206) is recently used for the photodegradation of cationic dyes within 120 min with 92.5% catalytic efficiency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[23][24][25] Moreover, flower-like Z-scheme nanostructures assembled from two-dimensional (2D) nanosheets feature interconnected open pores, thereby exposing a large number of active sites and ensuring high catalytic performance. 26,27 Ultrathin 2D nanosheets assembled into a flower-like structure in close contact with each other, thereby displaying high stability and reusability. 28 Recently, Zhang's group found that PDDA functionalized BP nanosheets combined with BiOI nanoplates displaying a unique flowerlike nanostructure with enhanced visible light photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%